2013
DOI: 10.14367/kjhep.2013.30.1.065
|View full text |Cite
|
Sign up to set email alerts
|

Development and Evaluation of Comprehensive Health Care Program for Infectious Disease Management in Child Care Centers by Doctor of Korean Medicine

Abstract: Objectives: The present study was carried out to develop and evaluate comprehensive health care program to prevent infectious disease and promote health in child-care centers by Doctor of Korean medicine. Methods: A nonequivalent control group pretest-posttest design study was conducted on 568 children and 85 child care teacher at 12 child care facilities for 12 weeks from July to October 2012. The program was consist of management, education, screening under concepts of traditional preventive medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…But one should note that most of preventive interventions were performed using Korean traditional herbal medicines according to the Korean traditional medicine theory. In addition, this result was just one aspect of evaluation and other comprehensive effects were also reported by Park et al [ 12 ], which showed the significant decrease in children's absence/lateness days and high parents' satisfaction with this intervention.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…But one should note that most of preventive interventions were performed using Korean traditional herbal medicines according to the Korean traditional medicine theory. In addition, this result was just one aspect of evaluation and other comprehensive effects were also reported by Park et al [ 12 ], which showed the significant decrease in children's absence/lateness days and high parents' satisfaction with this intervention.…”
Section: Discussionsupporting
confidence: 75%
“…This implies that the treated group visited physicians less, specifically 0.12 times less per person, controlling for observable covariates and unobservable time-invariant variables. This is an improved result compared with Park et al [ 12 ], which evaluated the same intervention based on survey and showed that the total medical care utilization due to infectious diseases decreased, but without statistical significance. On the other hand, drugs prescription days, antibiotics prescription days, and medical cost decreased, but not statistically significant.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…When looking at preceding research conducted by Park et al 22,23) , where the medical use, absence and leave, attitude of the teacher regarding the illness due to infectious diseases was measured before and after the program of having a Korean medical doctor at child care institutions, the research and design was similar to the following study, and the results also showed similar outcomes of the total number of medical use of children not showing statistically significant results but showed reduction in medical use. In a different preceding research 24) which focused on Korean medical house doctor programs on vulnerable children, the difference in difference analysis did not show statistically significant results but showed patterns of reduction in the number of medical use, and days of absence, early leave and tardiness, drawing similar conclusions.…”
Section: Further Considerationmentioning
confidence: 96%